Revisiting the Issue of Attribution of Some Catacomb Monuments Groups from the South of Eastern Europe in the Late 3rd – Early 5th Centuries - Vladimir Yu. Malashev; Mikhail V. Krivosheev (Нижневолжский археологический вестник)
The catacomb funerary ritual had a widespread occurrence among the southern Eastern European population in late Roman times and at the beginning of the Great Migration Period. The Alan culture monuments of the 2nd – 4th centuries AD from the North Caucasus and the “Alans-Tanaites” nomadic culture of the late 3rd – 4th centuries AD feature the burial ritual most widely and vividly. Evidently, the migration occurred in a westerly direction from the “Alan-Tanaitian” culture area in the late 3rd century, resulting in the appearance of a group of under-kurgan burials in the steppe zone of the Dniester-Danube interfluve. It is possible that the people who left these kurgans in the 4th century were assimilated by the Chernyakhov culture bearers and switched to a sedentary lifestyle, having lost the kurgan funeral ritual (Belen’koe burial ground) but retained the catacomb burial structure of almost predominantly type II. The catacomb burials under the kurgans graphically feature the Alans-Tanaites fate after the encounter with the Huns, who defeated and subjugated the Alans-Tanaites, partly incorporating the vanquished population into their military and political union. The Alans-Tanaites took part in the campaign in Transcaucasia and Western Asia as part of the Hunnic army (395–398), as evidenced by the specific forms of the catacombs in the kurgans of the Palasa-Syrt burial ground from the Western Caspian region. A group of kurgan catacombs in the Middle Don and the Left Bank of the Dnieper features the partial outflow of the Alans-Tanaites from the Volga-Don steppes under the pressure of the Huns in the course of their expansion. A part of the Alans-Tanaites participated in the movement of the Huns to the west, as evidenced by the catacombs in the Budzhak steppe dating back to the last quarter of the 4th century.